Role of hydrometeorological factors and solar activity in interannual variability of ice extent in the East Siberian Sea - L. A. Timokhov; V. E. Borodachev; I. V. Borodachev; N. A. Vyazigina; E. U. Mironov; M. Janout (Лëд и снег, 2019)
Interannual changes of the summer ice coverage were investigated, and the role of hydrometeorological factors and solar activity in long-period fluctuations of the ice area in the East Siberian Sea was determined. Multivariate statistical analysis of time series of the ice cover, hydrometeorological elements, and the solar activity (SA), was performed for the period from 1950 to 2012 with regard for the cross-correlations of the analyzed variables that made possible to develop the equations of interannual fluctuations of the ice coverage in the East Siberian Sea in August and September. The equations include the following variables: air temperature in June–August of the current year TVI‑VIII; the atmospheric circulation presented by indices of Arctic oscillation (Arctic Oscillation, AO), Arctic dipole (Arctic Dipole, AD), Pacific North American oscillation (Pacific North American Oscillation, PNA); average annual runoff of river waters into the Laptev and East Siberian seas (RivLES) with a time shift of one and two years; average annual index of the North Atlantic thermal state (AMO) with a time lag of eight years; solar activity SA, presented by the average annual Wolf number with advancing of one year. Diagnostic calculations of the ice area by the obtained equations using the actual values of the indices did show a good agreement between the actual and calculated values in August and September from 1950 to 2012. These equations were used to calculate contribution of each factor to the general dispersion of fluctuations of the ice coverage. The most important factors influencing the ice cover of the Sea in August and September are: the air temperature; the atmospheric circulation, presented by the Arctic Oscillation at the end of winter; and Atlantic waters which are characterized by AMO with a time lag of eight years. The role of other factors, i.e. summer atmospheric circulation, river runoff into the above seas, and 11-year cycle of solar activity were found to be equal to only 5–10% for each. Basing on these estimates, it has been concluded that the obtained statistical equations may be used as the diagnostic models of interannual changes in the ice coverage.